One‐year results of the first‐in‐man study investigating the Atrial Flow Regulator for left atrial shunting in symptomatic heart failure patients: the PRELIEVE study. (5th March 2021) - Paitazoglou, Christina; Bergmann, Martin W.; Özdemir, Ramazan; Pfister, Roman; Bartunek, Jozef; Kilic, Teoman; Lauten, Alexander; Schmeisser, Alexander; Zoghi, Mehdi; Anker, Stefan D.; Sievert, Horst; Mahfoud, Felix; et al.
Abstract: Aims: Attenuating exercise‐induced elevated left atrial pressure with an atrial shunt device is under clinical investigation for treatment of symptomatic heart failure (HF). Methods and results: PRELIEVE was a prospective, non‐randomised, multicentre, first‐in‐man study in symptomatic HF patients with reduced (HFrEF) or preserved (HFpEF) ejection fraction and pulmonary capillary wedge pressure (PCWP) ≥15 mmHg at rest or ≥25 mmHg during exercise. Here, we provide follow‐up data up to 1 year after implantation of the Atrial Flow Regulator (AFR) device. The AFR was successfully implanted in 53 patients (HFrEF n = 24 and HFpEF n = 29). Two patients were not enrolled due to an unsuccessful transseptal puncture. There was one device embolisation into the left atrium, which required surgical removal. One patient experienced a serious procedure‐related adverse event (post‐procedural bleeding and syncope). All patients with sufficient echocardiography readout confirmed device patency with left–right shunt both at 3 ( n = 47/51, 92%) and 12 ( n = 45/49, 92%) months. At 3 months, rest PCWP decreased by 5 (−12, 0) mmHg ( P = 0.0003, median Q1, Q3). No patient developed a stroke, worsening of right heart function or significant increase of pulmonary artery pressure. Six (6/53, 11%) patients were hospitalised for worsening of HF and three (3/53, 6%) patients died. We observed improvements in New York Heart Association functional class, 6‐min walking distance and quality of life (Kansas City Cardiomyopathy Questionnaire) in certain patients. Conclusions: Implantation of the AFR device in HF patients was feasible. No shunt occlusion, stroke or new right HF was observed during the 1‐year follow‐up, with clinical improvements in certain patients. Abstract : Analysis of the first‐in‐man PRELIEVE study indicates that implantation of the Atrial Flow Regulator (AFR) device was feasible and associated with improved haemodynamic and clinical outcomes up to 12 months in certain patients with symptomatic heart failure with reduced (HFrEF) and preserved (HFpEF) ejection fraction. 6MWD, 6‐min walking distance; CVP, central venous pressure; KCCQ, Kansas City Cardiomyopathy Questionnaire; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide; NYHA, New York Heart Association; PAPs, systolic pulmonary artery pressure; PCWP, pulmonary capillary wedge pressure.